Sistemas de costeo y la rentabilidad en las empresas del sector agrícola del cantón Daule - Cabrera Tejada, Enrique Andrés (2021)
The present investigation is about the treatment that given to the productive processes, that is, the treatment or techniques to handle each stage of conversion of materials into a final product. In this measure, the costing systems and the profitability that the company can obtain thanks to it, is what is going to be address in this study. In order to publicize the costing system, fundamental theoretical bases will be provide, which will allow the application of methodological tools to collect information in companies in the agricultural sector. It should be emphasized, the importance of treating each phase of production, by applying one of its systems to identify the economic benefits that could be obtained by investing in a new production order........